Peculiarities of translation of phraseological units in Honoré de Balzac's novel Father Gorio - N U Nelyubova; D S Komlach (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2012)
In the article we deal with the peculiarities of translation of phraseological units from French to Russian in Honoré de Balzac's novel Father Gorio, and we also compare their literary translation and the translation found in the phraseological dictionaries.